Albert Einstein - Wishinsky, Frieda (DK, 2005)
Presents a photographic introduction to the life and accomplishments of Albert Einstein, one of the most significant scientists of the twentieth century, discussing his boyhood, schooling, early career, family, and discoveries in the field of physics.